The Effect of Kinesiotaping on Temporomandibular Joint Dysfunction: a Literature Review - Ms. Marissa De Souza Eremita (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background Temporomandibular joint (TMJ) dysfunction is a broad term used to describe various conditions involving the joint like pain, reduced range of motion, stiff muscles of mastication, clicking or popping sensation in the jaw or a change in the way the upper and lower teeth fit together. The major causes for TMJ dysfunction can be myogenous, arthrogenous or due to disc displacement. Management of TMJ dysfunction includes occlusal splints, self care and lifestyle modification. Physiotherapy interventions include biofeedback, TMJ exercises, TMJ mobilization, electrotherapy modalities, splinting, kinesiotaping, and postural correction. Objective To review the effects of kinesiotaping on TMJ dysfunction. Methodology An extensive literature search was performed on various electronic and print databases like PubMed, Cochrane, Science Direct, Pedro. 888 articles were retrieved based on search strategies in which 5 studies fulfilling the eligibility criteria were reviewed and reported. Conclusion Literature review suggests that, kinesiotaping works as an adjunct and helps by reducing pain and increasing the jaw range of motion in individuals, but does not work by itself as a treatment method.